ASPECTS OF LEOPARD CORAL GROUPER (Plectropomus leopardus) REPRODUCTION IN INDONESIA - Retno Andamari; Sari Budi Moria Sembiring; Gusti Ngurah Permana (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Leopard coral grouper, Plectropomus leopardus is one of the most economically important finfish fish in Indonesia and the demand for the grouper is rapidly increasing in Asia and the Pacific. Grouper exports from Bali were 1,613 mt in 2001, 2,082 mt in 2002 and 2,861 mt in 2003. Understanding the reproductive biology of fishes is an important component in developing mariculture and in the management of capture fisheries. This study reports on the reproductive biology of 86 coral groupers collected from various locations in Indonesia. The length and weight of these fish were recorded and related to gonad development. There was a strong relationship between length and weight; weight being proportional to the length raised to the power (b value) 3.2. As the value of b was greater than 3, this suggests that growth is allometric. Histological analysis 73% of the fish were immature, 19% were in transition from females to males, only 4% were male, and only 2 fish (2%) had mature gonads: these were female. The sex of 2 fish could not be determined. From these data it can be seen that the leopard coralgrouper has asynchronous gonad development. The two fish that were mature contained 343,980 and 429,259 oocytes and three distinct sizes of oocytes could be found. This suggests that the grouper is a multiple spawner. If fish are required for brood stock, this study has shown that only those with a length greater than 35 cm in standard length should be taken from the wild.